THE COLOR CHANGE EFFECT OF THERMOPLASTIC NYLON AFTER IMMERSION IN 30% KELAKAI (Stenochlaena palustris) LEAF EXTRACT - Rahmad Arifin; Vony Oktamillenia Putri; Renie Kumala Dewi (FKG ULM, 2024)
Background: The most commonly used denture cleanser is alkaline peroxide, but this type of denture cleanser can cause color changes of the denture base and is relatively expensive, so alternative denture cleansers from natural ingredients are needed. Kelakai leaves have an antifungal property that can be used as a natural-based denture cleanser. Purpose: To determine the color change effect of the thermoplastic nylon after immersion in 30% kelakai leaves extract. Methods: This study used a true experimental method with pre-test and post-test and control group design. The research used 24 round-shaped samples with 20 mm diameters and 3 mm thickness. There were 3 groups of immersion, including 30% kelakai leaf extract, alkaline peroxide, and distilled water. Results: The results showed the mean of color changes score for kelakai leaf extract (3,71), alkaline peroxide (2,59), and sterile distilled water (2,29). Data were analyzed using One Way ANOVA and Post Hoc Bonferroni. Conclusion: It can be concluded that there is an effect on color change of thermoplastic nylon immersed in 30% kelakai leaf extract, alkaline peroxide, and sterile distilled water. The highest to the lowest mean of color changes score was 30% kelakai leaf extract, alkaline peroxide, and distilled water. Keywords: Color changes, kelakai leaf extract 30%, thermoplastic nylon